1998
DOI: 10.1108/19355181199800001
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing, Corporate Performance, and Shareholder Wealth

Abstract: Restructuring events, such as downsizing, can either halt a downward spiral in corporate performance or perpetuate that downward spiral (Lindsley, Brass and Thomas 1995). This dual nature of downsizing is reflected in the mixed results found by prior researchers.We recognize the dual nature of downsizing by categorizing events according to the firm’s financial condition preceding the announcement of the downsizing. We find a significant negative stock price reaction for firms that are financially healthy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
10
0
4
Order By: Relevance
“…The possibility of information leakage has been noted in other studies (Franz et al 1998;Chatrath et al 1995;Brookman et al 2007). Additionally, Lee (1997) questioned if large shareholders in Japan can Layoff announcements and intra-day market reactions 217 respond to layoff announcements beforehand because they may have access to relevant information before the news is made public.…”
Section: Market Reactions To Final Decisionsmentioning
confidence: 57%
See 2 more Smart Citations
“…The possibility of information leakage has been noted in other studies (Franz et al 1998;Chatrath et al 1995;Brookman et al 2007). Additionally, Lee (1997) questioned if large shareholders in Japan can Layoff announcements and intra-day market reactions 217 respond to layoff announcements beforehand because they may have access to relevant information before the news is made public.…”
Section: Market Reactions To Final Decisionsmentioning
confidence: 57%
“…Examples of negative news include declining sales, money losses, unexpected lower earnings, signals that the firm and/or its growth opportunities are in a more precarious state than previously thought, closure of plants or facilities, negative revision of future operating prospects, new information about adverse market conditions, or an insufficient layoff (Worrell et al 1991;Lin and Rozeff 1993;Chatrath et al 1995;Palmon et al 1997;Elayan et al 1998;Chen et al 2001;Capelle-Blancard and Couderc 2006;Hillier et al 2007). Negative market reactions have been observed in studies by Worrell et al (1991), Lin and Rozeff (1993), Lee (1997), Elayan et al (1998), Franz et al (1998), Hallock (1998), Chen et al (2001), Nixon et al (2004), CapelleBlancard and Couderc (2006), and Hillier et al (2007). Last, Goins and Gruca (2008) found that layoff announcements result in a negative but statistically nonsignificant market reaction.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 87%
See 1 more Smart Citation
“…31 Abraham (2004); Collett (2002); Clarenbach und Davies (2001); Wertheim und Robinson (2000); Pouder et al (1999); Ray und Forsyth (1999u. 2002; Franz et al (1998); Elayan et al (1998); Davidson et al (1996); ; Worrell et al (1991). 32 Lediglich die Studie von Worrell et al (1991) kommt diesbezüglich zu abweichenden Ergebnissen.…”
Section: Abnormale Renditen Deutlich Vor Dem Ankündigungstag Eines Peunclassified
“…33 Während Franz et al (1998) und Collett (2004 signifikant positive DKAR in den ersten ein bis zwei Jahren nach dem Ereignis ausweisen, stellen , Ray und Forsyth (1999 und Abraham (2004) für eine Zeitspanne von bis zu zwei Jahren nach der Ankündigung signifikant negative DKAR fest. In den Untersuchungen von Worrell et al (1991), Davidson et al (1996), Pouder et al (1999) und Chen et al (2001) verändern sich die DKAR nach einem PAP-Plan außerhalb eines engen Zeitintervalls um das Ereignis nicht signifikant negativ oder positiv.…”
Section: Abnormale Renditen Deutlich Nach Dem Ankündigungstag Eines Punclassified